THE FORMATION OF THE IMAGE OF THE DOG IN UZBEK AND ENGLISH FOLKLORE (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article analyzes the historical, spiritual, and artistic formation of the image of the dog in Uzbek and English oral folklore. As one of humanity’s oldest companions, the dog has been reflected in the collective consciousness as a symbol of loyalty, protection, love, and at times, evil or betrayal. In Uzbek folklore, the image of the dog is predominantly associated with faithfulness, trust, and devotion, often linked with religious and mythological layers. In English folklore, however, this image appears as a symbolic representation of the spiritual world, witchcraft, loyalty, and the miraculous. The article provides a comparative analysis of the common and national characteristics of the image of the dog as reflected in both nations’ oral traditions.